EXPERIMENTAL MEASUREMENTS IMPACT OF SWITCHING FREQUENCY FOR THE MOSFET CONTROL SIGNAL ON THE ELECTROMAGNETIC INTERFERENCES IN A SERIES CHOPPER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Static converters consist of electronic switches, passive components (inductor, capacitor), and resistors, allowing the conversion of electrical energy from one form to another. However, the uses of semi-conductor components (MOSFET, IGBT, Thyristor, etc.) in switching are generating rapid variations of voltage (dv/dt) and current (di/dt). This leads to high-frequency electromagnetic disturbances. This paper presents the study of electromagnetic disturbances conducted in common and differential modes in a series chopper by simulation using LTspice software. Experimental measurements validate the obtained results. Then, we studied the impact of variation of the switching frequency on the input current and the output voltage of the chopper, as well as on the disturbances conducted in two modes, common mode, and differential, by experimental measurements in the time and frequency domains. An Arduino program does these variations on the control signal parameters.
Keywords: Switching frequency; Electromagnetic interference; Serial chopper; Differential mode; Common mode